USE OF MODERN TECHNOLOGIES IN TEACHING PHYSICS - Oltinoy Kodirova (International Scientific and Current Research Conferences, 2022)
This article discusses use of modern technologies in teaching physics. The material presented divided into topics, which, as a rule, considered in one lecture. The lecture presents the main experimental facts and formulates laws. Simple examples demonstrate their application. For independent work, literature and a list of questions recommended. Testing the results of independent work carried out according to a scheme similar to testing the degree of assimilation of lecture material.